2022
DOI: 10.31219/osf.io/aqwpn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality, Intelligence, and Academic Achievement: Charting their Developmental Interplay

Abstract: Although intelligence and personality traits have long been recognized as key predictors of students’ academic achievement, little is known about their longitudinal and reciprocal associations. Here, we charted the developmental interplay of intelligence, personality (Big Five) and academic achievement in 3,880 German secondary school students, who were assessed four times between the ages 11 and 14 years (i.e., in grade 5, 6, 7, and 8). We fitted random-intercept cross-lagged panel models (RI-CLPs) to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…However, due to the anonymization of the data, we could not investigate the role of individual di erences with respect to learner characteristics, as no participant-specific information was available. Therefore, future research may expand on our study by considering individual learner characteristics such as motivation, personality, cognitive abilities, prior academic achievement, socioeconomic status, or math anxiety (e.g., Bardach et al, 2023;Meyer et al, 2023) and their e ects on learning trajectories within ITSs (Hilz, Guill, Rolo , Aldrup, & Köller, 2023;Hilz, Guill, Rolo , Sommerho , & Aldrup, 2023). In addition, it would be illuminating to combine the process learning data used in our study with students' self-reported learning behavior and emotional dynamics during learning, as well as other behavioral assessments (e.g., emotion recognition systems, eye-tracking, heart rate variability, EEG data) to dig even deeper into the details of mathematics learning with ITSs.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the anonymization of the data, we could not investigate the role of individual di erences with respect to learner characteristics, as no participant-specific information was available. Therefore, future research may expand on our study by considering individual learner characteristics such as motivation, personality, cognitive abilities, prior academic achievement, socioeconomic status, or math anxiety (e.g., Bardach et al, 2023;Meyer et al, 2023) and their e ects on learning trajectories within ITSs (Hilz, Guill, Rolo , Aldrup, & Köller, 2023;Hilz, Guill, Rolo , Sommerho , & Aldrup, 2023). In addition, it would be illuminating to combine the process learning data used in our study with students' self-reported learning behavior and emotional dynamics during learning, as well as other behavioral assessments (e.g., emotion recognition systems, eye-tracking, heart rate variability, EEG data) to dig even deeper into the details of mathematics learning with ITSs.…”
Section: Discussionmentioning
confidence: 99%